Example app and code for visualization of videos, observational data and/oraccelerometer recordings - Kembro, Jackelyn Melissa (2023)
Fil: Kembro, Jackelyn Melissa. Universidad Nacional de Córdoba. Facultad de Ciencias Exactas, Físicas y Naturales. Cátedra de Química Biológica; Argentina.